Ultrasonographic assessment of superovulatory response in crossbred malabari goats - Sandhya Achuthan (Department of Reproduction Gynaecology and Obstertrics, College Veterinary and Animal Science, 2007)
A study was conducted to monitor the ovarian changes ultrasonographically in response to the superovulatory treatment in the crossbred Malabari goats and to compare the sonological findings with the direct visual appraisal of the ovaries.